Physical fitness qualities of professional volleyball players: Determination of positional differences - Marques, M. C.; van den Tillaar, R.; Gabbett, T. J.; Reis, V. M.; González-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the anthropometric and strength characteristics of elite male volleyball athletes and to determine if differences exist in these characteristics according to playing position. A group of 35 professional male team volleyball players (mean ± SD age: 26.6 ± 3.1 years) participated in the study. Players were categorized according to playing position and role: middle blockers (n = 9), opposite hitters (n = 6), outside hitters (n = 10), setters (n = 6), and liberos (n = 4). Height, body mass, muscular strength (4 repetition maximum bench press and 4 repetition maximum parallel squat tests), and muscular power (overhead medicine ball throw, countermovement jump) were assessed. Significant differences (p < 0.05) were found among the 5 positional categories. The results indicated that the middle blockers and opposite hitters were the tallest and heaviest players, whereas the libero players were the lightest. Differences were also found in bench press maximal strength, with the middle blockers and opposite players significantly stronger (p < 0.05) than the setters and liberos. The setter positional group had significantly poorer (p < 0.05) parallel squat performances than the outside hitter and opposite hitter groups. No other significant differences (p > 0.05) were found among groups for the strength and power parameters. These results demonstrate that significant anthropometric and strength differences exist among playing positions in elite male volleyball players. In addition, these findings provide normative data for elite male volleyball players competing in specific individual playing positions. From a practical perspective, sport scientists and conditioning professionals should take the strength and anthropometric characteristics of volleyball players into account when designing individualized position-specific training programs.